Cadmium content of rice planted in Organic and conventional farming system - Anggita, Tristantia; Budianta, Dedik; Napoleon, Adipati (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2025)
The impact of agricultural activities such as the application of organic and chemical fertilizers will be causing a Cadmium (Cd) contamination. Information on the presence of Cadmium (Cd) both in the soil and Rice Plants in North Talang Ubi, Talang Ubi District, Penukal Abab Lematang Ilir of South Sumatera, Indonesia is still very limited and difficult to obtain for the issue of heavy metal of cadmium (Cd). This study aims to analyze the cadmium content in paddy fields with two different cultivation systems, namely organic and conventional farming systems. This research was a survey method and soil analysis conducted in two locations which were soil from Rejosari with organic farming system and other coming conventional farming system. The soil sampling was done from March 2023 to June 2023. The results of this study showed that the cadmium content in soil in the two cultivation systems is still below the cadmium quality standard, with the highest soil Cd content found 0.00478 mg/kg in the conventional cultivation system where the threshold limit is 0.5 mg/kg. The cadmium content of rice shoot and roots in the two cultivation systems was also still below the quality standards of cadmium, where the highest Cd content was found around 0.03303 mg/kg in the conventional cultivation system where the threshold limit was 0.1 mg/kg.